1997
DOI: 10.1021/es9607289
|View full text |Cite
|
Sign up to set email alerts
|

Atrazine Photolysis:  Mechanistic Investigations of Direct and Nitrate-Mediated Hydroxy Radical Processes and the Influence of Dissolved Organic Carbon from the Chesapeake Bay

Abstract: Direct and nitrate-mediated hydroxy radical photoprocesses were examined with respect to atrazine (2-chloro-4-ethylamino-6-isopropylamino-s-triazine) transformation. Irradiation (λ > 290 nm) of aqueous solutions of atrazine in the presence of nitrate, which generates • OH, yielded 20% of 6-amino-2-chloro-4-isopropylamino-s-triazine (CIAT), 10% of 6-amino-2-chloro-4-ethylamino-s-triazine (CEAT), 6% of 4-acetamide-2-chloro-6-isopropylamino-striazine (CDIT), 3% of 4-acetamide-2-chloro-6-ethylaminos-triazine (CDET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
101
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(112 citation statements)
references
References 28 publications
10
101
0
1
Order By: Relevance
“…The observed rates constants calculated from firstorder rate plots were 0.0960 d −1 and 0.6960 d −1 for direct and indirect photolysis. In the indirect process, the XOH are formed faster, thus the faster degradation rate [24]. This rate was similar to that calculated from the current research data, (0.0882 d −1 versus 0.0960 d −1 ).…”
Section: At and Al Biodegradation In Soil Microcosmssupporting
confidence: 89%
See 1 more Smart Citation
“…The observed rates constants calculated from firstorder rate plots were 0.0960 d −1 and 0.6960 d −1 for direct and indirect photolysis. In the indirect process, the XOH are formed faster, thus the faster degradation rate [24]. This rate was similar to that calculated from the current research data, (0.0882 d −1 versus 0.0960 d −1 ).…”
Section: At and Al Biodegradation In Soil Microcosmssupporting
confidence: 89%
“…During indirect and direct photolysis of a substrate, the adsorption of UV-visible light energy resulted in the formation of oxidants such as the hydroxy radical (XOH) [24], causing similar reactions as described above. The observed rates constants calculated from firstorder rate plots were 0.0960 d −1 and 0.6960 d −1 for direct and indirect photolysis.…”
Section: At and Al Biodegradation In Soil Microcosmsmentioning
confidence: 92%
“…In light of these results, fenitrothion was more rapidly photodegraded in pure water under indirect photolysis compared to direct photolysis. This result consistently with Torrents et al (1997) reported that in the presence of the nitrate, where the hydroxyl radical was readily formed, a faster degradation of atrazine was observed compared to direct photolysis in distilled water. Therefore, the differences in the degradation rate constant and half-lives of fenitrothion between the two aqueous media are attributed mainly to the presence of nitrate under indirect photolysis, which accelerates the degradation rate of fenitrothion compared with direct photolysis.…”
Section: Degradation Kinetics In Milliq Watersupporting
confidence: 92%
“…Recent evidence indicates that the nitrate ion also promotes the photochemical oxidation of trace organic compounds in water. As reported by Zepp et al (1987) and Torrents et al (1997), the photolysis of nitrate, which is present in natural water as a natural component, produces hydroxyl radicals. Although hydroxyl radicals can be produced by several mechanisms, including the photolysis of hydrogen peroxide, ozone, nitrite, and dissolved organic matters, several studies have pointed to nitrate as the key source of the hydroxyl radicals in natural waters (Brezonik, 1994).…”
mentioning
confidence: 75%
“…Hapeman et al [252] examined the reaction of HO reaction between atrazine and HO was determined as light from a xenon lamp. The products found were 20% attack on the ethyl group was favoured relative to HO 6-amino-2-chloro-4-isopropylamino-s-triazine, 10% 6-attack on the isopropyl group.…”
mentioning
confidence: 99%